Smart Tourism: Aksentuasi Kesiapan Homestay di Kawasan Ekonomi Khusus Tanjung Lesung, Pandeglang-Banten - Nurdin Hidayah (Media Wisata, 2020)
This study intends to obtain comprehensive information about Homestay facilities readiness within the Smart Tourism development framework in Tanjung Lesung Pandeglang, Banten. This study uses a qualitative research design with a phenomenographic approach. Data collection was carried out by interviewing existing stakeholders, observing homestays in the study area and studying documents related to the Homestay program and tourism digitizing. The results of the study show that 1) The homestay program within smart tourism framework in Tanjung Lesung is based on driving the economy and welfare of the host community; 2) Implementation of the homestay facilities development within smart tourism framework in Tanjung Lesung is carried out in four stages: conversion, renovation, revitalization, and new development; 3) The application of smart tourism in Tanjung Lesung is done with information technology through marketing programs such as online market places; Pokdarwis and 10 pilot tourism villages in the Indonesia Tourism Exchange Program (ITX)